Potret Kerukunan Pemuda Lintas Agama di Jawa Timur - M. Thoriqul Huda (Proceedings of Annual Conference for Muslim Scholars, 2018)
This study aims to provide an overview of the condition of youth harmony across religions in the province of East Java, through the organization of Youth Communication Forum of Interfaith Intergovernmental Province of East Java which is in coordination with FKUB East Java province. In this research the researcher used qualitative research method with ethnography analysis blade, qualitative research method of the researcher select to get deep data from the research object, that is member of communication forum of young generation between East Java faithful, by using in-depth interview method and directly involved in the atmosphere of harmony in this forum, then the results of the data from the field of researchers perform data analysis to obtain results that accurate data.From the results of observations and interviews in the field, the researchers managed to take some research results, among them are: First Youth Communication Forum Intergovernmental Among Religious People under the auspices of FKUB East Java province, the second there are some places and time (the field of harmony) FORKUGAMA in coordinating and keeping the atmosphere in harmony, including FORKUGAMA Office, Coffee Place, Social Media Group, and place of seminar or workshop.